2014 IEEE VIS International Workshop on 3DVis (3DVis) 2014
DOI: 10.1109/3dvis.2014.7160106
|View full text |Cite
|
Sign up to set email alerts
|

SPAROGRAM: The spatial augmented reality holographic display for 3D visualization and exhibition

Abstract: While the 3D graphics technique has found its place for the scientific visualization, especially for medical and biological applications, it has long been speculated that the 3D may not be so much effective as far as the conventional information visualization is concerned. We agree upon this view that the naive extension of the 2D visual forms to 3D is not a way to go. Instead, the computergenerated 3D virtual world will serve best when the virtual world is seamlessly integrated with the real 3D space. For an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Source: Kim et al (2014) This research has a goal to develop Holo-SDK-based media learning that is valid, practical, and effective to support the learning process at SMK Negeri 1 Tonjong in the multimeter introduction material for grade 10. This is expected to create media that is appropriate, according to experts, practical for students and teachers, and effective in supporting students in improving their learning achievement.…”
Section: Figure 1 Head Tracking Interaction Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Source: Kim et al (2014) This research has a goal to develop Holo-SDK-based media learning that is valid, practical, and effective to support the learning process at SMK Negeri 1 Tonjong in the multimeter introduction material for grade 10. This is expected to create media that is appropriate, according to experts, practical for students and teachers, and effective in supporting students in improving their learning achievement.…”
Section: Figure 1 Head Tracking Interaction Systemmentioning
confidence: 99%
“…The use of desktop-based AR as a medium for visualizing virtual models helps students make it easier to understand the material being studied and provides new experiences in learning (Afandi et al, 2019). Computer-generated 3D virtual worlds will work best when virtual worlds are seamlessly integrated with real 3D spaces (Kim et al, 2014). This desktop requires software to visualize effective 3D holograms using a Software Development Kit (SDK).…”
Section: Introductionmentioning
confidence: 99%
“…For example, several researchers have expanded the visualization space by placing additional displays that are physically separated from each other behind the half-mirror display in parallel, typically in the form of a multi-layered display (Akeley et al, 2004;Dünser et al, 2008;Prema et al, 2006). Also, Kim et al (2014) and Olwal et al (2005) applied 3D stereoscopic image on a halfmirror film to extend the visualization in 3D space and integrate it into the real environment naturally instead of just fixing visual forms on a flat screen. However, previous research findings FIGURE 1.…”
Section: Uses Of Half-mirror Displays For Visualizationmentioning
confidence: 99%
“…For this reason, previous studies on displaying stereo images showed that vergenceaccommodation conflicts could cause visual discomfort and poor stereo performance. As one way to solve this problem, several researchers suggested that rather than presenting images 227 HOLOBOX: AUGMENTED VISUALIZATION AND PRESENTATION WITH SPATIALLY INTEGRATED PRESENTER on a single focal plane, using multiple focal planes and placing images near the focal plane could eliminate vergence-accommodation conflicts and reduce visual fatigue (Kim et al, 2014;MacKenzie et al, 2012). In addition, after separating the 3D visualization space into front and back spaces in accordance with the depth position of the presenter, and displaying information accordingly on each screen, we can present accurate occlusion cues without a complicated rendering process (Fig.…”
Section: Augmented Presentation Spacementioning
confidence: 99%
See 1 more Smart Citation